The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/en15062023
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in MOF-Based Adsorbents for Dye Removal from the Aquatic Environment

Abstract: The adsorptive removal of dyes from industrial wastewater using commercially available adsorbents is not significantly efficient. Metal–organic frameworks (MOFs) offer outstanding properties which can boost the separation performance over current commercial adsorbents and hence, these materials represent a milestone in improving treatment methods for dye removal from water. Accordingly, in this paper, the recent studies in the modification of MOF structures in dye removal from the aquatic environment have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 195 publications
(240 reference statements)
0
18
0
Order By: Relevance
“…Among them, metal-organic frameworks (MOFs) have shown competitive adsorptive performance with the advantages of low cost, high removal efficiency, and recyclability. 3 In addition to dye contamination, hazardous explosive materials produced in various chemical industries also present contamination issues. The released combustible materials can react with light, heat, and pressure, causing significant damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, metal-organic frameworks (MOFs) have shown competitive adsorptive performance with the advantages of low cost, high removal efficiency, and recyclability. 3 In addition to dye contamination, hazardous explosive materials produced in various chemical industries also present contamination issues. The released combustible materials can react with light, heat, and pressure, causing significant damage.…”
Section: Introductionmentioning
confidence: 99%
“…As efficient adsorbents, porous materials, including zeolites and activated carbon, have received attention for removing organic pollutants. Among them, metal–organic frameworks (MOFs) have shown competitive adsorptive performance with the advantages of low cost, high removal efficiency, and recyclability 3 …”
Section: Introductionmentioning
confidence: 99%
“…MOFs are the new alternate adsorbents with cost-effective, high thermal stability, change of porosity size, and metal sites [ 12 ]. Several organic linkers which consist of heterocyclic compounds like pyridine, pyrazole, imidazole, and triazole rings along with the carboxyl group play a vital role to establish hydrogen bonding; also, a π−π stacking interaction sites between MOFs and the organic pollutant, therefore, enables adsorption process [ 13 ]. In the literature survey, a comparative study on the adsorption efficiency of Mn-UiO-66, GONH2, and Mn-UiO-66@GO-NH 2 composites revealed that CR adsorption was 243.08, 292.99, and 486.17 mg/g respectively for 120 min with 50 mL of 100 ppm Congo red and 10 mg of adsorbents [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing different MOFs as adsorbents and photocatalysts, some of which have just been described, is one potential method. 43 Supercapacitors are one such electrochemical device that has surfaced with the potential to enable significant advancement in energy storage. 47−49 Due to the structural flexibility of MOFs, studies on direct application as supercapacitor electrodes are uncommon and difficult.…”
Section: Introductionmentioning
confidence: 99%
“…It is still a big challenge to make MOF photocatalysts that are stable, reasonable, and efficacious. Utilizing different MOFs as adsorbents and photocatalysts, some of which have just been described, is one potential method. …”
Section: Introductionmentioning
confidence: 99%